Authentic Leadership in The Perspective of Islamic Education - M. Aqil Fahmi Sanjani; Sevia Diana Safitri; Musammil Lateh (Yayasan Avicenna, 2024)
This research aims to examine the concept of authentic leadership in the perspective of Islamic education, focusing on the values of integrity, honesty, trust, and harmony between personal values and the actions of leaders. The background of this research is rooted in the importance of leadership based on moral and spiritual principles in the context of education, especially in Islamic educational institutions, where such values can create a healthy, productive, and trusting work climate. This research uses a qualitative approach with the type of library research, which relies on the analysis of documents from various written sources, such as international journals, books, and relevant scientific articles. The findings show that integrity and honesty, which in Islam are represented by the concepts of sidq and trust, play a key role in building authentic leadership, which focuses not only on worldly achievements, but also on the well-being of the ummah and the balance between personal and social interests. This research contributes to understanding how Islamic concepts such as sincerity and tawakkal (surrender to Allah) can enrich and deepen our understanding of authentic leadership in the context of Islamic education, as well as provide guidance for educational leaders in applying authentic principles based on moral and spiritual values.